Metabolic syndrome response to walking training and low carbohydate diet in elderly - Michael Banoub Sorour; Nagwa Mohemed Badr; Nargis Albert Labib (Cairo : Michael Banoub Sorour, 2009)
The purose of this study was to determine the effect of walking training program combined with low carbohydrate diet on improving risk markers of the metabolic syndrome in elderly subjects . Forty elderly subjects considered as metabolic syndrome patients according to World Health Organization definition for metabolic syndrome participated in the study and were divided randomly into two equal groups (study group and control group)
Thesis (Ph.D.) - Cairo University - Faculty of Physical Therapy - Department of Physical Therapy for Cardiopulmonary and Geriatrics Disorders
Issued also as CD
Keywords: Low carbohydate diet; Metabolic syndrome; Walking Training